The Role of the IL-20 Subfamily in Glaucoma - Mary K. Wirtz; Kate E. Keller (Mediators of Inflammation)
Glaucoma is a common disease that leads to loss of peripheral vision and, if left untreated, ultimately to blindness. While the exact cause(s) of glaucoma is still unknown, two leading risk factors are age and elevated intraocular pressure. Several studies suggest a possible link between glaucoma and inflammation in humans and animal models. In particular, our lab recently identified a T104M mutation in IL-20 receptor-B (IL-20RB) in primary open angle glaucoma patients from a large pedigree. Several of the interleukin- (IL-) 20 family of cytokines and receptors are expressed in ocular tissues including the trabecular meshwork, optic nerve head, and retinal ganglion cells. The DBA/2J mouse develops high intraocular pressures with age and has characteristic optic nerve defects that make it a useful glaucoma model. IL-24 expression is significantly upregulated in the retina of these mice, while IL-20RA expression in the optic nerve is downregulated following pressure-induced damage. The identification of a mutation in the IL-20RB gene in a glaucoma pedigree and changes in expression levels of IL-20 family members in the DBA/2J mouse suggest that disruption of normal IL-20 signaling in the eye may contribute to degenerative processes associated with glaucoma.